ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS DITINJAU DARI SELF-CONFIDENCE SISWA SMP PADA MATERI STATISTIKA - Desak Ketut Permatasari; Alfisyahra Alfisyahra; Pathuddin Pathuddin; Rita Lefrida (Universitas Tadulako, 2025)
This study aims to describe the mathematical representation ability of junior high school students in terms of self-confidence on Statistics material. This research is a descriptive qualitative research method. This research was conducted at SMP Negeri 9 Palu with the research subject 3 students of class VIII C. The research design used in this research is a case study. The research instruments were questionnaires, written assignments of statistics mathematical representation ability test, and interviews. Data analysis techniques are done by reducing data, presenting data, and drawing conclusions. Representation ability can be seen from verbal, visual and symbolic aspects. The data credibility test used in this research is time triangulation. The results showed that students' mathematical representation ability was divided into 3 categories, namely having high, medium, and low mathematical representation ability. The conclusion of this study is that the level of self-confidence affects the level of students' mathematical representation ability.